Behavioral Responses to Supply-Side Drug Policy During the Opioid Epidemic - Simone Balestra; Helge Liebert; Nicole Maestas; Tisamarie B. Sherry (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate behavioral responses to a staggered disruption in the supply of prescription opioids across U.S. states: the introduction of electronic Prescription Drug Monitoring Programs (PDMPs). Using administrative datasets, we find PDMPs curtail the proliferation of prescription opioids. Physicians respond to monitoring on the extensive margin, limiting the number of patients to whom they prescribe opioids without adjusting dosage or duration. This decreases supply to long-term opioid users, who evade the restrictions by acquiring prescriptions from out-of-state prescribers and by substituting to heroin. This causes a surge in heroin overdoses, which offsets reductions in hospitalizations and deaths from prescription opioids.
Keywords: H75; I11; I12; I18; 330; prescription drugs; opioid crisis; heroin; prescription drug monitoring programs